VISIBILIZACIÓN DE LA PEDAGOGÍA DIALÓGICA JURÍDICA: UN GIRO HERMENÉUTICO EN LA FORMACIÓN DEL ABOGADO - Silvera Sarmiento, Astelio (2019)
This proposal seeks to establish strong conceptual relationships and connections between the classical postures of legal education in the context of Colombian law. The technique of the hermeneutical turn is seen as the mediation strategy of dialogue and dialogic pedagogy, from a methodology of construction of knowledge beyond the exercise of dialogue, transcending towards interdisciplinarity common knowledge to reach the transdisciplinarity of scientific knowledge. Construction of knowledge is regarded from a systemic linkage between the subject and context, fromtheir own structures of critical thinking, and this increases the capacity of joint planning, justified its natural dynamics, exerting a critical dialogue with the hegemonic models and to the emergence of models emerging.